Exploitation of heterosis in linseed (Linum usitatissimum L.): EXPLOITATION OF HETEROSIS IN LINSEED - NALINI TEWARI; ACHILA SINGH (Journal of Oilseeds Research, 2015)
Heterosis was estimated for 55 hybrids for eight different characters and was expressed as increase or decrease over superior parent. Hybrids in which R-17, Gaurav and Shubhra were involved as female parents and 1/76 and Shubhra as male parents exhibited highest positive heterosis for most of the characters. This indicated the presence of higher frequency of additive alleles in these parents. Hybrids viz., Gaurav x 1/76 and Shubhra x 1/76 were found superior in respect of seed yield/plant, primary branches/plant, number of capsules/plant and 100-seed weight.